Analisis keterampilan literasi digital peserta didik melalui penggunaan e-learning sekolahku di sekolah dasar - Ladiva Shyafa Putri Maharani; Siti Istiyati; Septi Yulisetiani (Didaktika Dwija Indria, 2024)
This research was conducted to investigate the digital literacy skills of elementary school students through the use of e-learning. The subjects were 27 fifth grade students of SD Islam Diponegoro Surakarta. This study is a qualitative descriptive study with a case study design. The sampling techniques used were purposive sampling. Data collection was done by observation, interview, and questionnaire. The validity test technique used was source triangulation and time triangulation. Data analysis used was interactive qualitative analysis. The results of this study are as follows: (1) from the aspect of information and data literacy, 81,49% of students were able to access, search, select, and understand the information or material in e-learning, (2) from the aspect of communication and collaboration, 85.18% of students were able to participate and share information in e-learning, (3) from the digital content creation aspect, 94.44% of students were able to create assignments and use the features in elearning (4) from the aspect of security, 85.19% of students were able to protect their privacy data in e-learning, and (5) from the aspect of problem-solving, 88.89% of students were able to overcome technical problems and provide answers to questions in e-learning. The study shows that the students have digital literacy skills through the use of e-learning which can be seen from the five aspects of the student’s digital literacy skills